HEALTH-RELATED QUALITY OF LIFE, BODY MASS INDEX, AND DISORDERED EATING AMONG STUDENTS DURING COVID-19 MOVEMENT CONTROL ORDER IN MALAYSIA: A CROSS-SECTIONAL STUDY - Ishak, Sharifah Intan Zainun Sharif; Arumugam, Presanna; Chin, Yit Siew (Journal of Public Health Research and Community Health Development, 2025)
Background: University students are a group particularly susceptible to being overweight and obese, as well as disordered eating (DE) behaviors that may infer their health-related quality of life (HRQOL). Purpose: To determine the associations of body mass index (BMI) and DE with HRQOL among university students in Selangor, Malaysia during Movement Control Order 1.0 and 2.0 due to COVID-19 pandemic. Methods: This cross-sectional study was performed among 189 university students in two universities in Shah Alam and Serdang, Selangor. This study utilized a self-administered questionnaire consisting of socio-demographic information, self-reported weight and height, Eating Attitudes Test (EAT-26) assessing the DE status and 36-Item Short Form Survey (SF-36) assessed the HRQOL. Results: The prevalence of overweight and obesity were 15.3% and 16.9%, respectively. Meanwhile, the prevalence of DE was 25.4%. BMI was not significantly correlated with DE (r=0.012, p=0.875). Among eight subscales of HRQOL, BMI was significantly correlated with general mental health (r=0.207, p=0.004) and bodily pain (r=0.153, p=0.036). Meanwhile, there was a significant association between DE with four subscales of HRQOL, which were physical functioning (r=-0.183, p=0.012), role limitations due to physical health (r=-0.155, p=0.033), role limitations due to emotional problems (r=-0.232, p=0.001) and general mental health (r=-0.214, p=0.003). Poorer general mental health was correlated with both higher BMI and higher DE. Conclusion: This study suggests the need to add the component of mental health, in addition to healthy body weight and eating behavior in future nutrition interventions to improve the HRQOL among university students.